The Effect of Temperature and Air Velocity on Drying Rate of Cracker Dough Using Cabinet Dryer: Pengaruh Variasi Temperatur dan Kecepatan Udara Terhadap Laju Pengeringan Adonan Kerupuk Menggunakan Cabinet Dryer - Fahruddin, A’rasy; Anom Isti , As’ad; Mulyadi; Tjahjanti, Prantasi Harmi (Procedia of Social Sciences and Humanities, 2022)
Drying is the heating process of food so that it reaches the water content of a certain material. This study aims to determine the drying rate and drying efficiency of wet crackers by using a dryer that is varied with variations in temperature and air velocity. The drying rate is the rate at which the water content of the specimen is reduced. In the drying rate test, it is obtained from the rate of reduction of the mass of the specimen due to evaporation of the water content in the specimen. The test was carried out in stages by adjusting the temperature to 60oC, 70oC, and 80oC with the air speed of the blower at 700 rpm, 1150 rpm, and 1600 rpm continuously. The test results show that the drying rate and drying efficiency are the most optimal as follows: a temperature of 80oC at a blower speed of 700 rpm produces a drying rate of 11.67 mg/min.